2015
DOI: 10.1175/mwr-d-15-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Characteristics and Orographic Enhancement of Lake-Effect Precipitation East of Lake Ontario and over the Tug Hill Plateau

Abstract: The final published version of this manuscript will replace the preliminary version at the above DOI once it is available.If you would like to cite this EOR in a separate work, please use the following full citation: Veals, P., and W. Steenburgh, 2015: Climatological Characteristics and Orographic Enhancement of Lake-Effect Precipitation east of Lake Ontario and over the Tug Hill Plateau. Mon. Wea. Rev. Abstract 1Lake-effect snowstorms east of Lake Ontario are frequently intense and contribute to 2 substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 42 publications
2
42
1
Order By: Relevance
“…This distribution is noted particularly near Lake Ontario (Jiusto and Kaplan 1972;Wilson 1977;Minder et al 2015;Veals and Steenburgh 2015), as was the case for an LLAP event on 11 December 2013. The present study focuses on this particular event, observed intensively as part of the Ontario Winter Lake-effect Systems (OWLeS) project (Kristovich et al 2016).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…This distribution is noted particularly near Lake Ontario (Jiusto and Kaplan 1972;Wilson 1977;Minder et al 2015;Veals and Steenburgh 2015), as was the case for an LLAP event on 11 December 2013. The present study focuses on this particular event, observed intensively as part of the Ontario Winter Lake-effect Systems (OWLeS) project (Kristovich et al 2016).…”
Section: Introductionmentioning
confidence: 64%
“…The presence of the ;600-m-high Tug Hill to the east of Lake Ontario (Fig. 2) likely contributes through orographic influence (Hill 1971;Alcott and Steenburgh 2013;Veals and Steenburgh 2015). This may contribute to the inland increase in the observed precipitation, as the NR site is 223 m higher in elevation than SC.…”
Section: The Llap Band Of 11 December 2013mentioning
confidence: 97%
See 2 more Smart Citations
“…Heavy snowstorms frequently impact the northwest Japanese coast and adjacent topography, disrupting transportation, contributing to structural damage and periods of elevated avalanche risk, and building a snowpack critical for regional water resources and winter tourism (Chechin & Pichugin, ; Eito et al, ; Nakai et al, ; Steenburgh, ). Much of this snowfall results from sea‐effect precipitation (e.g., Campbell et al, ; Eito et al, ; Magono et al, ; Mizukoshi, ; Murakami et al, ; Nakai et al, ; Tsuchiya & Fujita, ), a phenomenon closely related to lake‐, sea‐, and ocean‐effect precipitation in other regions of the world (e.g., Andersson & Nilsson, ; Kindap, ; Kristovich et al, ; Laird et al, ; Niziol et al, ; Norris et al, ; Steenburgh et al, ; Veals & Steenburgh, ). Sea effect over the SOJ occurs predominantly during the East Asian winter monsoon, which results from the interaction of the semipermanent Siberian High over northern Asia and the Aleutian Low in the Gulf of Alaska and features mean northwesterly flow over the SOJ during winter (Boyle & Chen, ; Dorman et al, ).…”
Section: Introductionmentioning
confidence: 99%